Atovaquone-Proguanil: A Promising Therapy for Persistent Relapsing Babesiosis - Mahum Shahid; Brendan Wechsler; Vinod Parameswaran; Mark Anthony Diaz (Case Reports in Infectious Diseases)
We report a challenging case of persistent relapsing babesiosis in an immunocompromised host that was successfully managed with atovaquone-proguanil (Malarone). Malignant B-cell transformation and immunosuppressants, such as rituximab, deplete normal B-cells which normally produce antibodies to combat Babesia infection. Treatment can be prolonged and challenging in immunocompromised hosts. Atovaquone-proguanil (Malarone) is a novel therapy that can be used as part of a salvage regimen in case antimicrobial resistance or failure exists. Weighing the risks and benefits of continuing cancer therapy treatment or reducing the level of immunosuppression may aid in treatment. These are just as important as the choice of antimicrobial therapy for effective treatment and eradication of Babesia infection, especially in immunocompromised hosts.